The EFFECT OF BUDGETARY PARTICIPATION ON BUDGETARY SLACK : THE ROLE OF MORAL REASONING AS A MODERATION VARIABLE - Dian Mustika; Nolita Yeni Siregar; Reva Meiliana; Rieka Ramadhaniyah (Faculty of Economics and Business University of Lampung, 2023)
Implementation of regional autonomy based on Law no. 32 of 2004 had a significant impact on the procedure for preparing the Regional Revenue and Expenditure Budget (APBD). A performance-based budgeting system enables local governments to identify and define performance indicators that are relevant to local conditions, so that budgeting can focus more on achieving the expected results. However, problems arise when the involvement of various parties increases in the budget preparation process. This study aims to analyze the effect of budgetary participation on budgetary slack in the management of the district government budget. South Lampung by using the role of moral reasoning as a moderating variable. This research is a quantitative research with a survey method using a questionnaire as a data collection medium which is distributed directly to apparatus directly involved in district budgeting. South Lampung. Sampling using purposive sampling, and obtained as many as 53 participants. The method of data analysis and hypothesis testing used is Structural Equation Modeling (SEM) using the WrapPls 7.0 software analysis tool. The results of this study indicate that budgetary participation has a positive effect on budgetary slack in district government budget management. South Lampung, On the other hand, the role of moral reasoning is proven to be able to moderate the relationship between budgetary participation and budgetary slack.